The Role of Magdalene Online Media Public Relations in Forming Public Awareness of Women's Advocacy - Zinda Adinta Sari; Ninis Damayani; Yanti Setianti (Peneliti.net, 2022)
The flow of information in this digital era, currently growing rapidly, one of which is marked by the birth of new media or commonly known as New Media. A type of media that requires the internet connection. The example is an online media, which is currently considered as a vital component of spreading the flow of information regardless of distance and time. The grouping of online media itself is divided into two types, namely mainstream and alternative online media. Magdalene is present as an alternative online media that focuses on inclusive journalism, different from mainstream online media. Magdalene uses the role of public relations in maintaning communication both within the organization and to the public, by definition public relations is a series or system of activities that focuses on creating communication methods to shaping a public opinion, with the aim of benefiting both parties, internal and public. In this study, the role of Public Relations for online media Magdalene is focused and implemented to build public awareness of their women's advocacy issues. Magdalene’s PR role is to function as a medium for conveying messages through various channels, including website, social media, podcast, and others. With the main objectives of instiling public understanding and awareness on various women’s advocacy issues. This research uses a qualitative methods, particularly by observation and in-depth interview with key informant from Magdalene. Overall, the implementation public relations in reporting content on Magdalene’s online media is in accordance with its main objective, namely to shaping public awareness. The conclusion is that Magdalene’s online media expected to sharpen its publications on various issues that are focuses journalism, in order to create a wider and more literate public awareness of Magdalene’s own core values.